(untitled) (Albayan Scientific Journal, 2023)
The study aims mainly to shed light on the relationship of the characteristics of the company under review to the quality of the audit process from the point of view of the external auditors working in the accounting and auditing offices. A random sample of (100) respondents was taken and (94) valid questionnaires were received for electronic analysis. The study relied on the use of the quantitative approach in data collection and analysis, and descriptive statistics were used to analyze the characteristics of the sample, and the analysis of the binary linear correlation coefficient was used to determine the relationship between the quality of the external audit and the characteristics of the company. The subject of the review, the coefficient of determination was also used to find out the effect of the independent variable on the dependent variable, and the results showed a strong direct relationship between the characteristics of the company under review and the quality of the external audit. The study recommended that the audit offices should pay attention to increasing and developing the professional and scientific competencies of the members of their offices, in order to gain them the industrial specialization strategy and a good knowledge structure about the relationship of the characteristics of the company under review to the quality of the external audit.